Salinity Indian Ocean Dipole: Another facet of the Indian Ocean Dipole phenomenon from satellite remote sensing - Wei Shi; Menghua Wang (Science of Remote Sensing)
Using satellite-measured sea surface salinity (SSS) from the Aquarius and Soil Moisture Active Passive (SMAP) missions since 2011, we show that SSS in the Equatorial Indian Ocean (EIO) experienced dipolar changes in the well-defined east EIO and west EIO regions during the Indian Ocean Dipole (IOD) events. Similar to the concepts of dipole mode Index (DMI) and biological dipole mode index (BDMI), a salinity dipole mode index (SDMI) is proposed using the same definition for the east and west IOD zones. The results show that the salinity IOD in this study is in general co-located and co-incidental with the sea surface temperature (SST) IOD and biological IOD in previous studies. In the positive IOD event in 2019, the SSS anomaly was >1 psu for most of the east IOD zone, while the average SSS in the west IOD zone was ∼0.2–0.3 psu lower than the climatology monthly SSS. The reversed SSS dipolar variability in the EIO was also found during the 2022 negative IOD event. The SSS anomaly difference between the east IOD zone and west IOD zone shows the same variation as the SST-based DMI and chlorophyll-a (Chl-a)-based BDMI. The in situ measurements show that, in the 2019 positive IOD event, the significant IOD-driven salinity change reached water depths at ∼70–80 m and ∼50 m in the east and the west IOD zones, respectively. Results also reveal that the salinity IOD is not only driven by the various ocean processes (e.g., upwelling, downwelling, propagation of the planetary waves, etc.), which are also the main driving forcing for the SST IOD and biological IOD, but also the precipitation and evaporation in the two IOD zones, especially in the west IOD zone. In addition to the traditional SST IOD and recently proposed biological IOD, the salinity IOD indeed features another facet of the entire IOD phenomenon.